Voriconazole-Loaded Nanohydrogels Towards Optimized Antifungal Therapy for Cystic Fibrosis Patients - Shaul D. Cemal; María F. Ladetto; Katherine Hermida Alava; Gila Kazimirsky; Marcela Cucher; Romina J. Glisoni; María L. Cuestas; Gerardo Byk (Pharmaceutics)
Background/Objectives: Filamentous fungi, in particular the species Aspergillus, Scedosporium, and Exophiala, frequently colonize the lungs of cystic fibrosis (CF) patients. Chronic colonization is linked to hypersensitivity reactions and persistent infections leading to a significant long-term decline in lung function. Azole antifungal therapy such as voriconazole (VRC) slows disease progression, particularly in patients with advanced CF; however, excessive mucus production in CF lungs poses a diffusional barrier to effective treatment. Methods: Here, biodegradable nanohydrogels (NHGs) recently developed as nanocarriers were evaluated for formulating VRC as a platform for treating fungal infections in CF lungs. The NHGs entrapped up to about 30 μg/mg of VRC, and physicochemical properties were investigated via dynamic laser light scattering and nanoparticle tracking analysis. Diameters were 100–400 nm, and excellent colloidal stability was demonstrated in interstitial fluids, indicating potential for pulmonary delivery. Nano-formulations exhibited high in vitro cytocompatibility in A549 and HEK293T cells and were tested for the release of VRC under two different sink conditions. Results: Notably, the antifungal activity of VRC-loaded nanohydrogels was up to eight-fold greater than an aqueous suspension drug against different fungal species isolated from CF sputum, regardless of the presence of a CF artificial mucus layer. Conclusions: These findings support the development of potent VRC nano-formulations for treating fungal disorders in CF lungs.